PP.28 Cervical Cerclage: Are All Techniques Successful?. (26th April 2013) - Bonney, EA; Atkinson, A; Lancaster, R; Walker, JJ; Simpson, NAB
Abstract : Objective: Preterm birth is a global public health issue. In women considered high risk, insertion of a cervical cerclage has been shown to reduce this risk. We present findings from a retrospective cohort evaluating the success of different cerclage procedures (Shirodkar, McDonald and Transabdominal) in a tertiary level obstetric unit. Study design: Retrospective data was collected for 200 women who underwent a cerclage procedure at Leeds Teaching Hospitals NHS Trust between August 2000 and October 2010. Exclusion criteria for the study included multiple pregnancy, insertion of more than one cerclage in a single pregnancy, or an incomplete data record. Success was measured by delivery of a live baby ≥ 34 weeks. Mean gestational age (MGA) for each group was also calculated. Statistical analysis was performed using Fisher's exact test. Results: The Shirodkar cerclage produced a significantly greater MGA at delivery (36.3 weeks), compared to both McDonald (33.5 weeks; p = 0.004) and transabdominal cerclage (33.3 weeks; p = 0.007). Elective insertion of Shirodkar, McDonald and Transabdominal cerclage was carried out in 70, 37, 25 women respectively. These produced success rates of 81.4%, 70.3% and 72% (Shirodkar vs McDonald p = 0.226, Shirodkar vs Transabdominal p = 0.393). Ultrasound-indicated sutures were placed in 48 women (Shirodkar n = 24, McDonald n = 24). The success rates were 92.7% and 66.7% respectively, however these were not significantly different (p = 0.0723). Conclusion: These results demonstrate consistent rates in births greater than 34 weeks gestation following insertion of cervical cerclage. Although Shirodkar cerclage appears preferable in elective and ultrasound-indicated procedures, prospective randomised trials such as MAVRIC1 need to be completed to confirm this. Reference: http://www.medscinet.net/mavric/default.aspx